Faktor-Faktor Yang Berhubungan Dengan Preeklamsi Pada Kehamilan Di Wilayah Kerja Puskesmas Muara Kelingi Tahun 2024 - Perawati, Perawati; Sari, Lezi Yovita; sari, Liya Lugita (Jurnal Kesehatan Mitra Sekawan, 2024)
Based on the Census Survey in 2015, the maternal mortality rate in Indonesia was 305 per 100,000 live births. Meanwhile, the projected neonatal, infant and under-five mortality rate based on the 2017 IDHS is 15 per 1000 live births. The target neonatal mortality rate at the IDHS in 2024 is 11.1% and the SDGs target in 2030 is 8.6% (Ministry of Health, 2019). according to Commission IX of the House of Representatives in South Sumatra, the number of maternal deaths in 2022 was 97 people, down from 131 people in 2021. For the number of infant deaths in 2022 there are 497 people or down from 2021 as many as 502 people. this study uses descriptive analytic research design with a cross sectional approach. The method that will be carried out by researchers is quantitative. The relationship between these variables is determined based on statistical tests using the Cross Sectional method. The results showed that there was a relationship between maternal age and the incidence of preeclampsia (p-value = 0.004; there was a relationship between parity and the incidence of preeclampsia (p-value = 0.000, there was no relationship between gameli and the incidence of preeclampsia (p-value = 0.122). It is hoped that the Muara Kelingi Community Health Centre can improve the ability of health workers and the quality of midwifery services in reducing the incidence of eclampsia, especially in mothers with age during pregnancy, parity, gameli, gestational age at high risk of preeclampsia should be closely monitored protein levels and blood pressure so that complications do not occur.